Dependent versus state-permeated capitalism: Two basic options for emerging markets - Andreas Nölke (International Journal of Management and Economics, 2018)
Can comparative capitalism (CC) assist us in understanding both the rise and the current challenges of emerging market capitalism? This article applies analytical instruments developed in CC scholarship on emerging markets to address this question. During the last two decades, CC scholarship - defined by common features such as the emphasis on institutional contexts that are sticky and most important at the national level - has evolved considerably. This contribution to the third generation of this scholarship highlights the degree of international economic integration as the central strategic choice to be faced by emerging economies. It does so by systematically comparing dependent market economies of East Central Europe with the state-permeated economies of China, India and Brazil. The core finding is that both types of capitalism have been able to mobilize substantial institutional complementarities during the last three decades but will face considerable economic and political challenges in the years ahead.
Keywords: 650; emerging markets; comparative capitalism; dependent market economies; state-permeated market economies